2001
DOI: 10.1039/b100552i
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of highly ordered Au nanowire arrays

Abstract: In this paper, we report the electrochemical fabrication of highly ordered Au nanowire arrays within hexagonal close-packed nanochannel alumina (NCA) templates with pore diameters ranging from 35 nm to 100 nm. The observations of TEM, SAED, and HRTEM show that single crystal Au nanowires have been obtained within the templates with 45 nm diameters. The growth mechanism of the single crystal Au nanowires is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…Such top-down approaches, however, are cumbersome and have a low yield, which hinders practical applications. High throughput approaches for the synthesis of metallic nanowires are thus intensely searched [44][45][46][47][48]. In general, the production of arrays of nanostructures on substrates by lithographic techniques presents the disadvantage of high cost and a restriction in the number of materials to which it can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Such top-down approaches, however, are cumbersome and have a low yield, which hinders practical applications. High throughput approaches for the synthesis of metallic nanowires are thus intensely searched [44][45][46][47][48]. In general, the production of arrays of nanostructures on substrates by lithographic techniques presents the disadvantage of high cost and a restriction in the number of materials to which it can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue cracks growing in the vacuum generally grew much more slowly, i.e., more cyclic damage was required to accumulate ahead of the crack tip (Figure 2.14). Previous studies have shown that long fatigue cracks grow more slowly in lower humidity environments [13, 141. The small fatigue cracks in the vacuum environment were found to propagate preferentially through persistent slip bands formed ahead of the crack tip as has been previously observed in cast Mg [18] and other alloys [25]. Fatigue cracks prefer to propagate along the persistent slip bands because these regions have been weakened by intense dislocation activity and cracking.…”
Section: Discussionmentioning
confidence: 52%
“…Local chemical composition was determined with Energy Dispersive X-ray (EDX) analysis. In-situ tests conducted in the SEM do not provide significantly more resolution as compared to other techniques such as replica methods [18], but allow both EDX analysis and imaging using backscattered electrons that can provide additional microstructural information. Completely reversed (R = Gmin/Gmax = -1) fatigue tests were performed at a displacement rate of 20 p d s .…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations